The Dilated Cardiomyopathy Related to Hyperthyroidism with Cardiogenic Shock and Inadequate Diuretic Therapy: A Case Report - Sudarmika, Kadek Adi; Bagiari, Ketut Erna; Pratama, I Gede Bagus Gita; Wulandari, Ni Luh Eka Sriayu (Cardiovascular and Cardiometabolic Journal (CCJ), 2024)
Highlights: 1. This article highlights the complexity of thyroid dysfunction and how individual assessments are crucial in determining the effective management of it. - Background: Dilated Cardiomyopathy (DCM) is a non-ischemic heart muscle disease characterized by structural and functional myocardial abnormalities. One of its causes is hyperthyroidism. Hyperthyroidism can lead to a hyperdynamic circulatory state, increasing cardiac output and metabolic demands, which can ultimately result in heart failure. Case Presentation: A 35-year-old woman presented with complaints of acute shortness of breath that worsened at night, accompanied by bilateral lower limb edema and palpitations. Physical examination showed low BP (84/60 mmHg), tachycardia 110 BPM, and elevated JVP. Auscultation detected fine bilateral crackles and mitral regurgitation. Echocardiography showed consistent with DCM. Conclusion: Effective management of heart failure in the context of thyroid dysfunction requires a multidisciplinary approach that encompasses the disease's cardiac and endocrine components. This case illustrates the complexity of treating DCM with hyperthyroidism and the need for individualized therapy to optimize patient outcomes. Managing cardiomyopathy related to hyperthyroidism presents unique challenges, as it requires treatment for both hyperthyroidism and heart failure, especially when cardiogenic shock is present with an inadequate response to diuretics. This case highlights the complex interaction between thyroid dysfunction and heart failure, as well as the therapeutic strategies used to manage this condition.